MODERNISASI DAN REFORMASI DALAM PEMBINAAN HUKUM ISLAM DAN PRANATA SOSIAL DI NEGARA ISLAM: Telaah Komparatif Indonesia dan Malaysia - Suhardin (Jurnal Al Tasyri'iyyah, 2022)
Abstrak :This paper discusses the modernization and reform of the development of Islamic law and social institutions in Islamic countries as a comparative study of Indonesia and Malaysia. Islamic law revealed by Allah aims to prevent confusion in the community and bring benefit to them, directing them to truth, justice and wisdom and explaining the path that must be passed. In this case, it is based on five main priorities, namely maintaining religion, soul, mind, lineage and property, based on the al-Qur'an which is universal and dynamic. Thoughts on the development of Islamic law have long been studied by Western historians, especially those who have a tendency to justify the authenticity of Islamic law. Because the legal theme has a relationship with reality and the physical environment, it inevitably has to face challenges related to the facts of social change. Meanwhile, modernism in Islam is a series of thoughts and schools of thought in ijtihad to think rationally and to change understandings or customs that must be adapted to developments and conditions that exist at this time, without leaving Islamic values. Therefore, opportunities are always open and must be carried out by taking into account the social implications of the application of the product of legal thought.